AN IMAGE OF AMERICAN MUSLIMS THROUGH UPDIKE’S TERRORIST: A STUDY OF IDENTIFICATION AND REPRESENTATION - Diba Prajamitha Aziz (Universitas Gadjah Mada, 2015)
In the aftermath of September 9/11 tragedy, an image of Muslim dramatically becomes popular topic and object for the researchers. Although analyses for the most part tend to explain the image of Muslim in negative and stereotypical tendency, the wave of action that expresses positive image of Muslim has surfaced in American society. In that case, this thesis using a novel to see that social phenomena attempted to reveal that an image of American Muslims as represented by Ahmad Ashmawy Mulloy in Updike’s Terrorist contributed to endorse an image of Muslim neither as extremist nor as terrorist. To achieve its purpose, firstly this study employs theory of imaginary and symbolic identification from Jacques Lacan. This theory is used to explain the impact of fatherless background, the presence of surrogate father and the influence of another figure on Ahmad. Secondly focusing on an image of American Muslims, theory of representation from Hall is applied. His theory is as a bridge that Muslim can be constructed and represented in the novel. Furthermore, opinions about extremist and moderate Muslim are used to explain those images through characteristics such as thought, action and orientation. The result of the study reveals that the process of identification divides people whom Ahmad had interaction into category of Muslim and non-Muslim group. Muslim group teaches Islamic identity to Ahmad and non-Muslim group plays big role to influence Ahmad to integrate himself into American society. Due to those groups, an identity and image of Ahmad is always related to the other. Focusing on Ahmad’s representation as American Muslim, he shows that there are three images such as extremist, transitional and moderate. As a result, through depicting Ahmad as moderate Muslim, Muslim is not terrorist.Keywords: American Muslim, identification, representation, extremist Muslim, moderate Muslim